2013
DOI: 10.1038/ki.2012.408
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deficiency of adiponectin protects against acute kidney injury

Abstract: Adiponectin is a multifunctional cytokine that has a role in regulating inflammation. Here we determined if adiponectin modulates ischemic acute kidney injury. Compared with wild-type mice, adiponectin knockout mice were found to have lower serum creatinine and less tubular damage or apoptosis following ischemia/reperfusion injury. This latter process was associated with decreased Bax and reduced activation of p53 and caspase-3. Targeted disruption of adiponectin was also found to inhibit the infiltration of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 50 publications
4
81
0
1
Order By: Relevance
“…The above-mentioned studies should be considered separately from studies investigating the role of adiponectin in the setting of acute renal injury. The latter group of studies includes two trials investigating whether adiponectin can modulate the adverse effects of renal ischemia-reperfusion injury in mice (Cheng et al 2012, Jin et al 2013. These studies yielded conflicting results with regard to the acute responses of various parameters of renal structure and function resulting from acute renal injury.…”
Section: The Role Of Adiponectin In Renal Physiologymentioning
confidence: 99%
“…The above-mentioned studies should be considered separately from studies investigating the role of adiponectin in the setting of acute renal injury. The latter group of studies includes two trials investigating whether adiponectin can modulate the adverse effects of renal ischemia-reperfusion injury in mice (Cheng et al 2012, Jin et al 2013. These studies yielded conflicting results with regard to the acute responses of various parameters of renal structure and function resulting from acute renal injury.…”
Section: The Role Of Adiponectin In Renal Physiologymentioning
confidence: 99%
“…6,7,17,42,43 Bone Marrow Transplantation Bone marrow transplantation was performed as previously described. 6,10,17,42,44 Briefly, bone marrow cells (5310 6 ) from WT or STAT6 KO mice were transferred to lethally irradiated WT mice. Chimeric mice were allowed to recuperate for 7-8 weeks before UUO surgery.…”
Section: Animals and Uuo Surgerymentioning
confidence: 99%
“…4) It has also been observed that the p53-Bax-caspase-3 apoptotic pathway is involved in renal I/R injury. 4,5) P53 can induce the downregulation of anti-apoptotic Bcl-2 and the upregulation of pro-apoptotic Bax. A decrease in the Bcl-2/Bax ratio triggers cytochrome c release from mitochondria, which results in the activation of caspase-3 and a chain reaction leading to apoptosis.…”
mentioning
confidence: 99%